Code clone detection and analysis in open source applications - Mubarak-Ali, A. F. (IGI Global, 2014)
Code clone is a portion of codes that contains some similarities in the same software regardless of changes made to the specific code such as removal of white spaces and comments, changes in code syntactic, and addition or removal of code. Over the years, many approaches and tools for code clone detection have been proposed. Most of these approaches and tools have managed to detect and analyze code clones that occur in large software. In this chapter, the authors aim to provide a comparative study on current state-of-the-art in code clone detection approaches and models together with their corresponding tools. They then perform an empirical evaluation on the selected code clone detection tool and organize the large amount of information in a more systematic way. The authors begin with explaining background concepts of code clone terminology. A comparison is done to find out strengths and weaknesses of existing approaches, models, and tools. Based on the comparison done, they then select a tool to be evaluated in two dimensions, which are the amount of detected clones and run time performance of the tool. The result of the study shows that there are various terminologies used for code clone. In addition, the empirical evaluation implies that the selected tool (enhanced generic pipeline model) gives a better code clone output and runtime performance as compared to its generic counterpart.